Vecākā pirmsskolas vecuma bērnu dialogrunas veidošanās radošajā rotaļā - Kozlovska, Līga (Latvijas Universitāte, 2017)
Kvalifikācijas darba tēma ir “Vecākā pirmsskolas vecuma bērnu dialogrunas veidošanās radošajā rotaļā”. Pētījuma mērķis – pētīt vecākā pirmsskolas vecuma bērnu dialogrunas veidošanās radošajā rotaļā. Pētījums sastāv no teorētiskās un empīriskās daļas. Teorētiskajā daļā tiek apskatītas pedagogu un psihologu atziņas, analizēta lomu rotaļu nozīme pirmsskolas vecuma bērnu dialogrunas veidošanos. Rotaļa ir ļoti nozīmīgs bērna audzināšanas un mācīšanās līdzeklis, kas veicina bērnam apgūt saskarsmes prasmes, veidot savstarpējas attiecības, attīstīt valodu, domāšanu, atmiņu, māca bērnu koordinēt savu darbību ar vienaudžu darbību. Bērns rotaļā, praktiski darbojoties, mācās un apgūst dialogrunas kultūru, iemācās kontrolēt savas emocijas, atdarināt. Empīriskajā daļā tiek atspoguļots pētījums par pirmsskolas vecuma bērnu dialogrunas veidošanos radošajā rotaļā. Ir izstrādāti dialogrunas vērtēšanas kritēriji, aprakstīts praktiskais darbs ar bērniem. Darbs sastāv no 46 lapaspusēm, darbam ir pievienoti 2 attēli, 4 tabulas un izmantoti 52 literatūras avoti. Atslēgas vārdi: runa, valoda, dialogruna, rotaļa, radošā rotaļa.

The theme is “The speech in a creative play of children with pre-school age.”. The aim of the study – to analize the speech in a creative play of children with pre-school age. The study shall consist of theoretical and empirical parts. In the first subparagraph, the (theoretical) is viewed educators and psychologists knowledge, explains the role play, and their role in the formation of pre-school age children. The game is a very important feature of child education and learning to learn, interpersonal skills, create child relationships, develop language, thinking, memory, teaches children to coordinate their activities with peers operation. In a practice game, learning the language and the context. The child is learning the game and learning dialog culture, learn to control his emotions, to imitate. In the second subparagraph of (empirical) a study on children of pre-school age dialog creative play. Role play is a great role in shaping dialog educator, if properly and systematically promote, support the child, if necessary, assist with advice, recommendation, allows the game does not interfere with the freedom of his creativity, and tells how to behave during the talks in the correct language. Educator is competent to engage children in conversation, through various means, to initiate a dialogue, to promote the ability to listen to the conversation, interrupting her, taught to express their thoughts. The work of the research methods used in the ratings: a literature analysis. The work is consist of 46 pages, 2 figures, 4 tables and 52 leterary sources have been added of tge work. Keywords : speech, language, dialogue, play, creative play.
The speech in a creative play of children with pre-school age
Keywords: Pirmsskolas pedagoģija; lk17033; lk17033; lk17033; lk17033; lk17033